Composting of Cow Dung, Garden Waste, and Market Waste using Local Microorganisms (LMO) through the Takakura Stacking Method - Rinanda, Bismi Lyra; Aziz, Rizki; Yenni (Indonesian Journal of Environmental Management and Sustainability, 2025)
One of the main challenges in agricultural practices is the heavy reliance on chemical fertilizers without being balanced by the use of organic fertilizers. This study aims to analyze the maturity, quality, and quantity of compost produced from a mixture of cow dung, garden waste, and market waste using the Takakura Layered Method with EM4 and Local Microorganisms (LMOs) as activators. The LMOs used included LMO A (tuna fish waste, sugarcane bagasse, and pineapple peel) and LMO B (tuna fish waste, banana peel, and vegetable scraps). Composting was conducted in duplicate with seven treatment variations: (A) cow dung with EM4, (B) cow dung with LMO A, (C) cow dung with LMO B, (D) cow dung mixed with garden waste and LMO A, (E) cow dung mixed with garden waste and LMO B, (F) cow dung mixed with garden and market waste with LMO A, and (G) cow dung mixed with garden and market waste with LMO B. The results showed that all treatments met the composting standards. All variations complied with the Indonesian National Standard (SNI 19-7030-2004) in both maturity parameters (pH, temperature, color, texture, odor, and composting duration) and quality parameters (moisture content, C-organic, nitrogen, C/N ratio, phosphorus, and potassium). The compost quantity was reduced by 27–58%. The best result was observed in variation (D1), which consisted of cow dung, garden waste, and LMO A, achieving a score of 39 with a composting time of only 6 days.